An analysis of weaning weight records in Kansas cowherds from 1968 to 1985 - Perry, R.C; Simms, D.D.; Corah, L.R.; Patterson, D.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A data set of 33,208 individual weaning records (1968-1985) from producers within Kansas was analyzed to determine factors influencing weaning weight. In determining the effect of calving sequence (21 day periods), only data from larger cowherds with records from at least 5 years were included (n=18,400). On the average, for every 21 days later a calf is born, there is a 22.8 lb decline in weaning weight. During the 17-year period that these records encompassed, there has been an average annual weaning weight increase of 4.6 lbs. This study suggests that factors influencing weaning weight in Kansas are age at weaning, month of birth, herd size, sex of calf and age of dam.
Keywords: Beef; Weaning weight; Cow-calf operation